Corporate blue : a novel presented in partial fulfilment of the requirements for the degree of Master of Arts in English, Massey University - Myers, Daniel (Massey University, 2002)
My first day on the job with those nutcases, I was greeted by the loser's end of a very large handgun. Were I a more intuitive man, I could have taken that as a sign to just turn around and walk away. Leave that place and never think of it again. It would've been the wise thing to do. In my own defence however, I could point out that I didn't have a lot of options as to where I could turn. The President of the United States, among others, was pissed-off with me. And I had promised myself that I would make the best of this new situation in a new country. In time-I figured a year max-I was sure they would all forgive me back in America and let me come home.